SELEKSI POHON PLUS PADA AREAL TEGAKAN BENIH IUPHHK-HA PT. SUKA JAYA MAKMUR KALIMANTAN BARAT - Juanda, .; Muin, Abdurrani; Wulandari, Reine Suci (Universitas Tanjungpura, 2017)
The availability of quality seed is an important factor in planting activities both in natural forests and Â forestplantations. Knowledge about the source of seed or the parents tree is an important part to getting good quality seeds.The aims of this study was to establish plus tree that haave several adventages phennnotype, such as grand in diameter,total height, branch free trunk, trunk straighness and surface, wide canopy, and the health of the tree as the the seed- producing trees.This research was conducted by the method of exploration, which is purposive sampling data retrieval using plus tree selection method. This method uses the comparison tree as a basis for determining candidate plus trees.The object of this study is that individuals mature trees with a diameter of at least 20 cm from other types of prospective (Dipterocarpaceae) contained in the Areal of Seed Stands. According to the research there are 49 candidates plus trees, 9 individuals of tree with the highest scores on a plot 92 YY32 km 128 Areal Seed Stand PT. Suka Jaya Makmur West Kalimantan. Assessment is the percentage difference and a score between plus trees with tree comparison, the result tree top with a score 92 found in tree numbers 91, 101, 122, 131, 134, 145, 179 tree species Shorea laevis, tree number 115 trees Shorea leprosula , tree number 153 trees Shorea parvifolia, the total height of a tree with a score of 20, bole height with a score of 15, the diameter of the stem with a score of 30, wide canopy with a score of 10, the surface of the rod with a score of 5, the alignment of the rod with a score of 7, and health tree with a score of 5.It means that most parent trees that exist in the area of stands Seed PT.Suka Jaya Makmur feasible to set as the Plus tree.Keywords: Dipterocarpaceae, Plus Tree, Selection, The Â Area of Seed Stands.